Staatsbürgerschaft und religiöse Pluralität in post-nationalen Konstellationen: zum institutionellen Wandel europäischer Religionspolitik am Beispiel der Inkorporation muslimischer Immigranten in Großbritannien, Frankreich und Deutschland - Koenig, Matthias (2003)
This study explores the religio-political dimensions of the changing logic of citizenship and its constitutive elements of membership, rights, and identity in the context of globalisation. It is based on comparative research on the patterns of symbolic and organisational incorporation of Muslim immigrant minorities in Britain, France and Germany in the period of 1973-2001. Differences between these three cases in the incorporation of Islam, as evinced by integration policies and educational policies, are explained by historical path-dependencies, notably by institutional patterns of state-church relationships (state-church, separation, co-operation) and the religious factor in the process of national-building. On the other hand, one can observe a successive convergence of incorporation patterns of Muslim minorities in European public spheres, exemplified by various discourses of inclusion and exclusion; to account for these trends, reference is made to the changing cultural and structural features of the world polity as theorised by sociology's neo-institutionalism. It is argued that the world polity model of the nation-state, which is epitomised by the coupling of political organisation and collective identity and is articulated in the institution of national citizenship, has undergone significant changes in the post-War era. These can best be captured by the de-coupling of political organisation and collective identity, and by the decomposition of the constitutive elements of citizenship. It is further argued that this global transformation is inducing new religious politics which is characterised by the inclusion of "religion" as a legitimate category of identity in the public sphere. Thus, as European democracies are facing claims for the public recognition of particularistic religious identities whose legitimacy can be derived from universalistic human rights discourses, they are increasingly developing new institutional arrangements of religious diversity. Immigration from Muslim countries in Western Europe has therefore been one of the major factors contributing to political transformation and, hence, to a re-interpretation of the European vision of political modernity with in a global context.
Markburg, Univ., Diss., 2003. Zugriffs-Datum 16.12.2009
Keywords: Frankreich; Deutschland; Großbritannien; Hochschulschrift; Einwanderung; Muslim; Staatsangehörigkeit; Religionspolitik